Diagnosis of Scrotal Mass in Children - Axel P. Lumi; Harsali Lampus; Nathaniel Pali (Universitas Sam Ratulangi, 2022)
Abstract: Scrotal mass is one of the diseases in the urology field with a moderately high prevalence. Problems with the contents of scrotum vary, ranging from infections, tumors, to fluid. Diagnosis of scrotal mass is based on detail ananmnesis, systematic physical examination, and other supporting examinations. Scrotal ultrasound can confirm the exact location of a mass and rule out the presence of an inguinal hernia. Scrotal masses in adults require a formal examination with serum tumor markers, scrotal ultrasound as needed, and immediate consultation with a urologist for staging and further intervention. Scrotal masses in children are much less common than in adults and should be evaluated by a urologist.Keywords: scrotal mass; childrenÂ Abstrak: Massa skrotum merupakan salah satu penyakit di bidang urologi dengan prevalensi yang cukup tinggi. Masalah pada isi skrotum bervariasi, mulai dari infeksi, tumor, hingga cairan. Â Diagnosis massa skrotum ditegakkan melalui anamnesis yang cermat, pemeriksaan fisik terarah, dan pemeriksaan penunjang. Ultrasonografi (USG) skrotum dapat mengonfirmasi lokasi yang tepat dari suatu massa sekaligus menyingkirkan adanya hernia inguinalis. Massa testis pada dewasa memerlukan pemeriksaan formal, dengan penanda tumor serum, USG skrotum sesuai kebutuhan, dan konsultasi segera dengan ahli urologi untuk staging dan intervensi lebih lanjut. Massa skrotum pada anak jauh lebih jarang daripada dewasa dan harus dievaluasi oleh seorang ahli urologi.Kata kunci: massa skrotum; anak